Genome assembly and annotation of Babesia rossi, a protozoan parasite for canine babesiosis - Neelam Redekar; Xu Wang; Luis Neves; Steven Brooks; Justin Lack; Andrew Leisewitz; Hans Ackerman (BMC Genomics)
Abstract Background Apicomplexan parasite, Babesia rossi, is an Ixodid tick-transmitted pathogen that causes the most severe form of canine babesiosis disease. Compared to other Babesia pathogens of dogs, B. rossi exhibits unique pathophysiology, virulence, and a responsiveness to drugs that differs from the small Babesia parasites. Results Here we report the first near-complete chromosome-level assembly of Babesia rossi strain PMB – isolated from a sick dog from Pietermaritzburg, South Africa. Assembly with long-read HiFi data yielded 21.06 Mbp genome size, spanning across five gene-dense chromosome-level scaffolds, a single apicoplast scaffold, and a remaining 54 unplaced low gene density scaffolds with 1.32 Mb N50 and 96.6% BUSCO Apicomplexan completeness. The genome annotation identified a total of 3,098 protein-coding genes, 71 tRNA, and 16 rRNA genes. The mitochondrial genome (6.4 Kbp) was also identified. Genome assemblies of two additional field isolates of B. rossi were also reported. Comparative genomic analyses revealed four syntenic genomic inversions and multiple polymorphisms across three B. rossi isolates, although SNP and indel density was higher within the gene desserts of the genomes. Despite these differences, three B. rossi isolates’ genome assemblies showed 99% conserved orthologous gene sets. About 76% of protein-coding genes of Babesia rossi isolate PMB were shared with four other Babesia species. Conclusion This report provides valuable genomic information that is crucial to comprehend B. rossi evolution, virulence, and potential drug targets for canine babesiosis.